Widespread Occurrence of Black-Orange-Black Color Pattern in Hymenoptera. Issue 2 (11th March 2019) - Mora, R; Hanson, P E
Abstract: Certain color patterns in insects show convergent evolution reflecting potentially important biological functions, for example, aposematism and mimicry. This phenomenon has been most frequently documented in Lepidoptera and Coleoptera, but has been less well investigated in Hymenoptera. It has long been recognized that many hymenopterans, especially scelionids (Platygastridae), show a recurring pattern of black head, orange/red mesosoma, and black metasoma (BOB coloration). However, the taxonomic distribution of this striking color pattern has never been documented across the entire order. The main objective of our research was to provide a preliminary tabulation of this color pattern in Hymenoptera, through examination of museum specimens and relevant literature. We included 11 variations of the typical BOB color pattern but did not include all possible variations. These color patterns were found in species belonging to 23 families of Hymenoptera, and was most frequently observed in scelionids, evaniids, and mutillids, but was relatively infrequent in Cynipoids, Diaprioids, Chalcidoids, and Apoids. The widespread occurrence of this color pattern in Hymenoptera strongly suggests convergent evolution and a potentially important function. The BOB color pattern was found in species from all biogeographic regions and within a species it was usually present in both sexes (with a few notable exceptions). In better studied tropical regions, such as Costa Rica, this color pattern was more common in species occurring at lower elevations (below 2, 000 m). The biology of the tabulated taxa encompasses both ecto- and endoparasitoids, idiobionts and koinobionts, from a diversity of hosts, as well as phytophagous sawflies.